2021
DOI: 10.25122/jml-2020-0112
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mouthwashes on fluoride dentifrices in preventing dental abrasion or erosion

Abstract: Erosive tooth wear (ETW) refers to the chemical dissolution of mineralized tissues by acids of non-bacterial origin. It occurs in the primary as well as the permanent dentition. In this study, our objectives were to investigate and compare the impact of chlorhexidine gluconate (CHX), essential oils (EO), and cetylpyridinium chloride (CPC) on ETW protection produced by conventional fluoride kinds of toothpaste. A clinically relevant in-vitro erosion/abrasion pH cycling model was employed to test the effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Hasil penelitian yang telah dilakukan peneliti menunjukkan bahwa sebagian besar ibu hamil (83,6%) masih memiliki pemahaman yang kurang terkait penggunaan mouthwash setelah menyikat gigi. Penggunaan obat kumur dengan efek antimikroba terbukti efektif melawan karies gigi, gingivitis, dan periodontitis [37]. Klorheksidin (dalam konsentrasi 0,05-0,2%) adalah bahan aktif antiseptik yang terdapat dalam berbagai jenis obat kumur dan termasuk dalam FDA kategori B yang berarti bahwa cukup aman untuk janin [38].…”
Section: Metode Penelitianunclassified
“…Hasil penelitian yang telah dilakukan peneliti menunjukkan bahwa sebagian besar ibu hamil (83,6%) masih memiliki pemahaman yang kurang terkait penggunaan mouthwash setelah menyikat gigi. Penggunaan obat kumur dengan efek antimikroba terbukti efektif melawan karies gigi, gingivitis, dan periodontitis [37]. Klorheksidin (dalam konsentrasi 0,05-0,2%) adalah bahan aktif antiseptik yang terdapat dalam berbagai jenis obat kumur dan termasuk dalam FDA kategori B yang berarti bahwa cukup aman untuk janin [38].…”
Section: Metode Penelitianunclassified
“…Thyme oil showed antiviral properties against the Herpes simplex virus and had bacteriostatic and antimicrobial effects [ 28 , 48 ]. Citrus fruits such as sweet orange, bitter orange, lemon, lime, grapefruit, bergamot, yuzu, and kumquat are found to be effective as medicinal agents in mouthwashes, too; they have the following properties: anti-tumor, antibacterial, antifungal, larvicidal, antioxidant, anti-carcinogenic, and anti-inflammatory effects, but the data based on oral pathology are not shown yet [ 89 , 90 ]. Other studies concluded that even if the natural-based mouth rinses have plaque-inhibitory potential, the gold standard remains CHX-based mouthwashes [ 87 , 91 , 92 ].…”
Section: Main Bodymentioning
confidence: 99%